Comparative Study on the Regeneration of Fe3O4@Graphene Oxide Composites - Hu, Zhongliang; Zhang, Xiaojing; Li, Jingying; Zhu, Yirong (Frontiers in Chemistry, 2020)
In this study, two kinds of graphene oxide (GO) sheets wrapped magnetic nanoparticles composites were used to investigate their regeneration. The composites have similar core-shell structures, but the interactions connecting the core and shell are quite different, which are electrostatic and covalent, respectively. The composites were characterized by scanning/transmission electron microscopy, power X-ray diffraction, and vibrating sample magnetometer analysis. The morphologies and structures of the samples during regeneration had been revealed using methylene blue and Pb(II) as adsorbates. The results showed that the composites with covalent bonding could maintain stable structure and have a good regeneration performance for adsorption-desorption of methylene blue and Pb(II). For the sample with electrostatic interaction, it could approximately preserve its core-shell structure and could be recyclable for adsorption-desorption of methylene blue, however, it would disintegrate its core-shell structure, thus greatly decreasing its adsorption capacity of Pb(II) after regeneration. The regeneration mechanisms of the composites were analyzed and it could provide a useful theoretical guide to design the GO sheets wrapped magnetic nanoparticles.